The Concept of Age in The English Language: Definition, Varieties, and History of Development - Abduraimova Madinaxon Dilshodjon qizi (Scientific Trends, 2024)
The article is devoted to the study of the concept of "age" in the English language, its essence, varieties and history of development. The work considers the concept from the point of view of cognitive linguistics, where age is interpreted as a multi-level mental formation that includes both objective and subjective aspects of the perception of time and life stages. Particular attention is paid to the lexical and semantic means of expressing age, such as words and phraseological units, as well as metaphorical models through which the symbolic perception of the life path in English-speaking culture is manifested. The article analyzes the key stages of the historical study of the concept of "age", starting with lexicographic studies of the 19th century and ending with the cognitive -linguistic and sociocultural approaches of the present.
Keywords: Age concept, English language, cognitive linguistics, lexical-semantic analysis, metaphorical models, cultural stereotypes, history of development.